A neurose obsessiva na mulher: entre a exceção e a castração - Mello, Marcelo Francisco de (2012)
This work begins with a clinical case, so its method is mainly clinical and falls within the tradition of fundamental psychopathology, a discipline which seeks a bailout of human subjectivity, believing that since the creation of the General Psychopathology proposed by Jasper (1913), the human subjectivity has been deprecated instead of an objectivist psychopathology that aims to observation of human suffering through technological mechanisms for classification. The clinical method is the one adopted by the Fundamental Psychopathology, so psychoanalysis is more suitable for such discipline. Within this theoretical-clinical, this work refers to the involvement of obsessive neurosis in a woman. Such manifestation finds little support in the current theory, enabling the importance of this production. The construction of the narrative of the cited case reveals theoretical, clinical and transferential barriers, which the author conducts a possible detailed study the most. The desire, its cause and its impossible of accomplishment were brought to the fore, as well as the constitution of the feminine in rescuing the eternal question: anatomy is destiny or not?